The microvariation of post-verbal negative particles in Old Gallo-Romance: a comparative study - Lloyd, AJ (2021)
This thesis is a microvariational analysis of post-verbal negative particles in varieties of Old Gallo-Romance between the years 1100 and 1500 A.D. It examines the internal and exogenous factors contributing to the survival of certain particles and the disuse of others. Using a mixture of verse and prose data from six oïl varieties and ten oc varieties of Old Gallo-Romance, it draws comparisons between them from the following perspectives: rates and degrees of grammaticalisation; the influence of discourse-pragmatics and information-structure on their presence, absence and frequency of occurrence; their diatopic and diachronic spread; and the effect that standardisation, linguistic prestige, and a scribal koiné had on the diminishing number of competing post-verbal negative particles in the grammar. In essence, it seeks to clarify why pas, as one of several hundred so-called ‘minimisers’, came to be the default sentential negator in French, rather than any other competing variant.